Fitness Measurements of Evolved Esherichia coli - Miskinyte, Migla (2014)
Bacteria can adapt very rapidly to novel selective pressures. In the transition from commensalism to pathogenicity bacteria have to face and adapt to the host immune system. Specifically, the antagonistic interaction imposed by one of the first line of defense of innate immunity cells, macrophages, on commensal bacteria, such as Escherichia coli (E. coli), can lead to its rapid adaptation. Such adaptation is characterized by the emergence of clones with mutations that allow them to better escape macrophage phagocytosis. Here, we describe how to quantify the amount of fitness increase of bacterial clones that evolved under the constant selective pressure of macrophages, from a murine cell line RAW 264.7. The most widely used assay for measuring fitness changes along an evolutionary laboratory experiment is a competitive fitness assay. This assay consists of determining how fast an evolved strain outcompetes the ancestral in a competition where each starts at equal frequency. The strains compete in the same environment of the evolution experiment and if the evolved strain has acquired strong beneficial mutations it will become significantly overrepresented in repeated competitive fitness assays.